The Moroccan Constitutional Transition: The Method of Contextualization and Mutual Interaction - Alicino, Francesco 20./21. Jh. (Religion and human rights, 2015)
In this article the author analyses the influence of Islamic references in the 2011 Moroccan constitutional reform that, far from taking place in a vacuum, was informed both by an internal political perspective and by the broader context of what has come to be called the “Arab Spring”. It will be outlined that, on the one hand, Islamic legal tradition interacts with Western legal principles; while on the other hand the exceptionalism of the “Moroccan Spring” reveals that those very principles are contextualized and adapted within this executive Islamic monarchy.